Analisis Pengaruh Intellectual Capital, Good Corporate Governance dan Competitive Advantage Terhadap Company Value Pada PT Bukit Asam Tbk Tahun 2016-2021 - Lisda Anggraeni; Saladin Ghalib (Universitas Lambung Mangkurat, 2023)
This study aims to analyze the influence of Intellectual Capital (X1), Good Corporate Governance (Z1), Competitive Advantage (Z2) on Company Value (Y), at PT Bukit Asam Tbk. The research was conducted using data for a period of 6 years, namely the period 2016-2021. The data source is secondary data which is analyzed through Partial Least Square (PLS). The test results show that there is a significant and positive influence on Intellectual Capital (X1) on Competitive Advantage (Z2). With a total influence of 71.3%. The use of Intellectual Capital in the company is able to increase the company's superior value or Competitive Advantage which makes it a characteristic of competitive advantage in the eyes of shareholders and industrial market players compared to other companies. Keywords: Intellectual Capital, Good Corporate Governance, Competitive Advantage, Company Value